Li adsorption, hydrogen storage and dissociation using monolayer MoS2: an ab initio random structure searching approach1. Issue 17 (7th May 2015) - Putungan, Darwin Barayang; Lin, Shi-Hsin; Wei, Ching-Ming; Kuo, Jer-Lai
<x xml:space="preserve">Abstract</x> Utilizing ab initio random structure searching, we investigated Li adsorption on MoS2 and hydrogen molecules on Li-decorated MoS2.